Canada: variations on a common theme (Italian Journal of Public Health, 2010)
Canada faces health care challenges common to all industrialized countries – how to ensure timely access tohigh quality care, close to home, at an affordable cost. Addressing these challenges is complicated by inter-jurisdictional variation in both how health care is managed and delivered, and in health outcomes. Canadacan be described as a non-system of 10 provincial and three territorial health insurance plans which mandatepublicly-funded coverage for medically necessary hospital and physician services, based upon commonprinciples and shaped by a federal governance structure that affords substantial power and autonomy to theprovinces/territories over matters of health and health care. This article first examines the structural contextof the health care system in Canada, including the range of services publicly funded, the public-private mix,and the complexities of current governance arrangements. It then discusses several issues affecting healthpolicy reform: costs versus access; questions of sustainability, quality, and performance; human resourcescapacity; and the provision of public and population health services.
Keywords: Canada; health care; federalism; primary health care; public health